Alternative Oxidase Inhibition Impairs Tobacco Root Development and Root Hair Formation - Liu, Yang; Yu, Lu-Lu; Peng, Ye; Geng, Xin-Xin; Xu, Fei (Frontiers in Plant Science, 2021)
Alternative oxidase (AOX) is the terminal oxidase of the mitochondrial respiratory electron transport chain in plant cells and is critical for the balance of mitochondrial hemostasis. In this study, the effect of inhibition of AOX with different concentrations of salicylhydroxamic acid (SHAM) on tobacco root development was investigated. Here we found that AOX inhibition significantly impaired the development of main root and root hair formation of tobacco. The length of main root of SHAM-treated tobacco was significantly shorter than that of the control and no root hairs were formed after treatment with a concentration of 1 mM SHAM or more. Transcriptome analysis showed that AOX inhibition by 1 mM SHAM involved in the regulation of gene expression related to root architecture. There was a total of 5855 differentially expressed genes (DEGs) were obtained compared SHAM-treated roots with the control. Of these, gene expression related to auxin biosynthesis and perception were significantly down-regulated by 1 mM SHAM. Likewise, genes related to cell wall loosening, cell cycle, and root meristem growth factor1 (RGF1) also showed down-regulation upon SHAM treatment. Moreover, combine with the results of physiological measurements, transcriptome analysis demonstrated that AOX inhibition resulted in excessive accumulation of ROS in roots, which further induced oxidative damage and cell apoptosis. It is worth noting that when indoleacetic acid (IAA, 20 nM) and dimethylthiourea (DMTU, 10 mM) were added to the medium containing SHAM, the defects of tobacco root development were alleviated, but to a limited extent. Together, these findings indicated that AOX-mediated respiratory pathway plays a crucial role in tobacco root development, including root hair formation.